The Wolves of Mercy Falls: Shiver - Book 1 - Stiefvater, Maggie 1981- (New York : Scholastic Press, 2009)
In all the years she has watched the wolves in the woods behind her house, Grace has been particularly drawn to an unusual yellow-eyed wolf who, in his turn, has been watching her with increasing intensity.
Keywords: Wolves -- Fiction; Metamorphosis -- Fiction; Supernatural -- Fiction